1998
DOI: 10.1007/s002800050784
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan (CPT-11) in combination with weekly administration of cisplatin (CDDP) for non-small-cell lung cancer

Abstract: The value of weekly administration of CDDP in combination with CPT-11 was shown by (1) diarrhea not being dose-limiting, (2) mild nausea, (3) well-maintained AUC of free platinum, and (4) promising activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…In a phase II study of irinotecan and cisplatin in patients with stage IIIB or IV disease, the response rate was 52% and the median survival time was 52 weeks (Masuda et al, 1998). In order to develop a more effective regimen, studies have been conducted in which the dose intensity of irinotecan and/or cisplatin has been increased (Masuda et al, 1994;Kobayashi et al, 1998;Ueoka et al, 2001), and in which various triplet-drug combination therapies using irinotecan, cisplatin, and another drug have been explored (Shinkai et al, 1994). Ifosfamide is an analogue of cyclophosphamide and shows significant activity against NSCLC (Costanza et al, 1978).…”
mentioning
confidence: 99%
“…In a phase II study of irinotecan and cisplatin in patients with stage IIIB or IV disease, the response rate was 52% and the median survival time was 52 weeks (Masuda et al, 1998). In order to develop a more effective regimen, studies have been conducted in which the dose intensity of irinotecan and/or cisplatin has been increased (Masuda et al, 1994;Kobayashi et al, 1998;Ueoka et al, 2001), and in which various triplet-drug combination therapies using irinotecan, cisplatin, and another drug have been explored (Shinkai et al, 1994). Ifosfamide is an analogue of cyclophosphamide and shows significant activity against NSCLC (Costanza et al, 1978).…”
mentioning
confidence: 99%
“…In the weekly administration of both CPT-11 and CDDP conducted by Kobayashi et al under similar consideration (Kobayashi et al, 1998), the most prominent toxicity was leukopenia, and diarrhoea was not a dose-limiting toxicity. CPT-11 has been considered as the major cause of diarrhoea in this combination.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that SN-38G is transformed to active SN-38 by bacterial beta-glucuronidase 18) . In reports from us and other researchers, damage in the small intestine was observed in humans 7,19) where little bacteria exist and, therefore, another key of CPT-induced diarrhea was considered.…”
Section: Discussionmentioning
confidence: 99%